9th International Congress of the Brazilian Geophysical Society 2005
DOI: 10.3997/2214-4609-pdb.160.sbgf430
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial F-region irregularities generated by the Rayleigh-Taylor instability mechanism – rocket observations from Brazil

Abstract: Several sounding rockets carrying plasma diagnostic experiments were launched from the Brazilian rocket launching stations in Natal (5.9 • S, 35.2 • W Geog. Lat.) and Alcântara (2.31 • S, 44.4 • W Geog. Lat.). Langmuir Probes (LP) were used to measure the height profiles of electron density and electron temperature and High Frequency Capacitance (HFC) probes were used to measure electron density. The LP's were also used to measure the amplitude of electron density fluctuations.A detailed study of the character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In accordance with Huba and Joyce (2007) simulations, such diffusion can result in its complex evolution with multiple bifurcations on both its walls. Muralikrishna and Vieira (2007) also suggest that the cascade process linked with the large‐scale upwellings could generate SIs via cross‐field instability and GDI. Studies by Garcia et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with Huba and Joyce (2007) simulations, such diffusion can result in its complex evolution with multiple bifurcations on both its walls. Muralikrishna and Vieira (2007) also suggest that the cascade process linked with the large‐scale upwellings could generate SIs via cross‐field instability and GDI. Studies by Garcia et al.…”
Section: Discussionmentioning
confidence: 99%
“…Often secondary instabilities (SIs) are seen to develop on the walls of nonlinearly growing equatorial plasma bubbles (EPBs) (Hysell, 2000; Huba & Joyce, 2007; Li et al., 2021; Muralikrishna & Vieira, 2007; Zalesak et al., 1982). Numerous radar and optical airglow observations from the Northern Hemisphere have shown their development on the west wall of an eastward drifting depletion (EDD) (Kelley et al., 2000; Makela, 2006; Mukherjee, 2003; Mendillo & Baumgardner, 1982; Rodrigues et al., 2018; Rohrbaugh et al., 1989; Tsunoda, 1983, 2015; Tsunoda & White, 1981; Tsunoda et al., 1982, 2011; Xiong et al., 2018; Yokoyama et al., 2014, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, EPB occurrences vary from day‐to‐day (Sharma et al., 2014). This phenomenon has been extensively investigated for decades using various equipment such as the incoherent back scatter radar, all‐sky imager and satellites (Immel et al., 2004; Mukherjee et al., 1997; Muralikrishna and Vieira, 2007; Sharma et al., 2014; Tsunoda, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that the seeding by these waves becomes pertinent in the solstice months, when the post sunset rise (PSSR) of the F layer is weak (Tsunoda, ). Muralikrishna and Vieira () reported that a higher F region base is preferable for R‐T instability to operate. Ossakow et al () presented a numerical simulation study, showing that the injection of an artificial depletion at the bottom side of the F layer can cause ESF to occur.…”
Section: Introductionmentioning
confidence: 99%